Is too much foreign aid a curse or blessing to developing countries? - Chala Amante Abate (Heliyon, 2022)
The aim of the study was to examine the relationship between amount of aid received and economic growth of developing nations and the role of quality of institutions and economic freedom in shaping the relationship between the two. To this effect, a panel data from 2006 – 2019 was gathered from 48 developing countries and an innovative dynamic panel threshold regression was used for estimation. Accordingly, it is found in this study that the relationship between aid and economic growth is nonlinear and U shaped, which shows the presence of threshold value of aid amounting 7.03% of GNI. The results further reveal that aid stimulates economic growth when the sampled developing countries attain a minimum institutional quality threshold of -0.320. As regards to the role of economic freedom, it is found that the overall economic freedom index of 53.481 should be attained to avoid undesirable effect of aid on economic growth. Therefore, the author recommends that donors should advance sufficient amount of aid to developing countries if they are really committed to support their economy. Recipient developing countries should improve up on the existing institutional setup and improve economic freedom indicators in order to get the best out of aid.